VIEWS ON REFLEXIVITY IN THE WORKS OF EASTERN THINKERS (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2026)
The problem of reflexive processes, such as self-awareness, self-management, self-control, self-understanding, self-knowledge, self-education, has been widely studied by encyclopedic scholars of the East, foreign and Uzbek psychologists. In particular, in the works of Abu Ali ibn Sina, Yusuf Khos Hajib, Abu Rayhan Beruni, Unsurulmaoni Kaykovus, Alisher Navoi, Jalaluddin Davani, and Abdurahman Jami, a number of ideas were put forward regarding the reflexive processes of personality and related characteristics.